1995
DOI: 10.1017/s1355617700000102
|View full text |Cite
|
Sign up to set email alerts
|

Simple reaction time as a measure of global attention in Alzheimer's disease

Abstract: Alzheimer's disease (AD) is characterized by progressive decline in memory, language and other cognitive functions. Deficits in attentional processes have also been suggested. A simple reaction time (RT) task was used to assess global attention in AD. The length and consistency of a warning signal given prior to the response stimulus were manipulated to determine if patients with AD and age-matched controls benefit from predictability in RT tasks. Overall reaction time was slower in the AD group than in the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
3
19
0
Order By: Relevance
“…The diversity (interindividual variability) in RT performance was greater for groups with AD and a-MCI than for the cognitively healthy controls. This observation is consistent with previous reports on AD 47 and other neurological disorders. 48 The clinical presentation of AD can be heterogeneous, which is most obvious at the early stages of the disease.…”
Section: Performance Variabilitysupporting
confidence: 94%
“…The diversity (interindividual variability) in RT performance was greater for groups with AD and a-MCI than for the cognitively healthy controls. This observation is consistent with previous reports on AD 47 and other neurological disorders. 48 The clinical presentation of AD can be heterogeneous, which is most obvious at the early stages of the disease.…”
Section: Performance Variabilitysupporting
confidence: 94%
“…These data are consistent with those of others who have shown deficits in DMTS task performance in participants with an AD diagnosis (Fowler et al, 2002;Money et al, 1992;Plaza et al, 2012;Sahakian et al, 1988;Sano et al, 1995). Notable aspects of DMTS task performance seen here in persons with a diagnosis of AD include significantly reduced speed of responding to both the sample stimuli (during which time processes such as encoding and discrimination should be important) and the choice stimuli (which should reflect functions perhaps more related to recall).…”
Section: Short-term Nonverbal Memorysupporting
confidence: 91%
“…For example, Hoogendijk et al [14] reported mean noradrenaline concentrations in the locus ceruleus significantly below those of controls. These findings, together with evidence from previous studies showing disrupted responses to warning stimuli in AD [15,16], led us to hypothesise that the alerting function of visual cues would be disrupted by this disease process.…”
Section: Introductionmentioning
confidence: 65%
“…The results from our previous study [1], which employed exactly the same visual cues to measure the validity effect (the difference in reaction times between targets occurring at the cued location compared to the not-cued location), showed that these cues produce a greater validity effect in individuals with AD, thus suggesting that these participants could process the cue appropriately. Our data indicates that at a time interval (200 ms) at which young and older people respond efficiently to warning cues, people with AD do not, possibly because the alerting effect is present in AD but takes longer to develop [15,16], producing inefficient processing of and response to, rapid changes in the environment.…”
Section: Discussionmentioning
confidence: 80%